Sleep and Marijuana Use - Brendan Jamieson; Sarah Martey; Jimmy Gilliam; Amy Adkins; Kenza Benkirane (OSF Registries, 2022)
This study examines correlations between sleep quality and marijuana use amongst a survey group of university students at Virginia Commonwealth University.
Keywords: Social and Behavioral Sciences